(untitled) (Revista de Ciências Agroveterinárias, 2020)
The accelerated aging test is a considerably important method for measuring the physiological potential of seeds. This study sought to apply the accelerated aging test to determine the vigor of red clover seeds of the Quiniquelli and Estanzuela 116 cultivars under water and salinity stress conditions. Accordingly, the seeds were aged for 12, 24, 36, 48, and 72 hours at 42 °C in water and a saturated salt solution (40% NaCl) and then assessed by the accelerated aging test. The lengths of 15 normal seedlings from each of the four replicates for both cultivars were measured, and the seedlings’ dry mass (48 h/60 °C) was determined. After aging 12, 24, and 36 hours in a saturated salt solution, vigor was above the average of 84.5% for both cultivars. In the test conducted with water, 36 hours were enough to stress the seeds. The accelerated aging time that best represented the vigor of the seeds of the Quiniquelli and Estanzuela 116 cultivars was 48 hours at 42 °C in the saturated NaCl solution, thus being the most suitable for red clover seeds.